2020
DOI: 10.1088/1361-6439/abc52f
|View full text |Cite
|
Sign up to set email alerts
|

Development of mechanically-robust piezoelectric micromachined ultrasonic transducer based on island-shaped monocrystalline PZT thin film partially covered with polyimide

Abstract: This paper describes a new design of piezoelectric micromachined ultrasonic transducer (pMUT) with a monocrystalline Pb(Zr,Ti)O3-based thin film (Mono-PZT) for enhancing the mechanical robustness. In this study, we investigated two design concepts to suppress crack generation in Mono-PZT. First, the area of Mono-PZT is limited by leaving an island Mono-PZT pattern only on the membrane of the pMUT. Second, the edge of Mono-PZT is covered with a polyimide (PI) thin film as a protection layer to prevent the peeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The resonant frequency of the ringshaped PMUT was found to be insensitive to the mean radius. Thao et al [35] designed an island-shaped PMUT with a monocrystalline PZT-based thin film for improving the mechanical robustness. The robust mechanical analysis of the PMUT was carried out by driving resonantly and increasing the displacement of the membranes.…”
Section: Pmut Structuresmentioning
confidence: 99%
“…The resonant frequency of the ringshaped PMUT was found to be insensitive to the mean radius. Thao et al [35] designed an island-shaped PMUT with a monocrystalline PZT-based thin film for improving the mechanical robustness. The robust mechanical analysis of the PMUT was carried out by driving resonantly and increasing the displacement of the membranes.…”
Section: Pmut Structuresmentioning
confidence: 99%
“…The bottom electrode fully covered the Si layer, while the optimal diameter of the top electrode was investigated through simulation to maximize its actuation ability. A polymer insulation layer is patterned to cover the edge of the PZT to prevent PZT from peeling from the edge [13].…”
Section: Designmentioning
confidence: 99%
“…Thus far, most of the previously reported pMUTs have a design in which a transducer material and a driving electrode are formed at the center of a vibrating diaphragm [13][14][15]. However, it is questionable whether this design is optimal for improving both the resonance frequency and displacement sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We prototyped a mono-PZT-based pMUT, and successfully demonstrated that it could provide high performance with a high signal-to-noise ratio. [30][31][32] However, such a monocrystalline thin film exhibits weak mechanical robustness. Theoretically, monocrystalline materials without defects are intrinsically robust.…”
Section: Introductionmentioning
confidence: 99%